Identivikasi dan Analisis Risiko Menggunakan Pendekatan ISO 31000 Studi Kasus Toko Berkah Bandung - Aisyah Humayyrah; Putri Dewi Renggani; Indy Fauziah Hanifa; Ari Assrishan Sosh Mantoro; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to identify, analyze, evaluate, and formulate risk treatments at Toko Berkah Bandung, a local retail MSME, using the ISO 31000 risk management framework. A descriptive qualitative case study was applied, utilizing observations, interviews, and business documentation. The findings reveal 40 risk events categorized into market, marketing, financial, operational, human resources, and legal risks. Risk evaluation indicates that most risks fall within moderate to high levels, while several are classified as extreme, including unstable cash flow, inaccurate inventory records, rising supplier prices, and digital reputation issues. Through ISO 31000, appropriate risk treatment strategies—such as risk reduction, avoidance, transfer, and acceptance—can be prioritized and implemented. The study highlights the necessity of operational digitalization, employee competency development, stronger financial governance, and regulatory compliance to enhance business resilience and sustainability.